2022
DOI: 10.3389/fimmu.2021.807093
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of mRNA-Seq and MiRNA-Seq Reveals the Molecular Mechanism of the Intestinal Immune Response in Marsupenaeus japonicus Under Decapod Iridescent Virus 1 Infection

Abstract: The intestine is not only an important digestive organ but also an important immune organ for shrimp; it plays a key role in maintaining homeostasis. Decapod iridescent virus 1 (DIV1) is a new type of shrimp-lethal virus that has received extensive attention in recent years. To date, most studies of the shrimp intestinal immune response under viral infections have relied on single omics analyses; there is a lack of systematic multi-omics research. In the current study, intestinal mRNA-seq and microRNA (miRNA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 99 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…In addition, some amino acid metabolism-related pathways were also significantly enriched under DIV1 infection, including “tyrosine metabolism”, “phenylalanine metabolism” and “alanine, aspartate and glutamate metabolism”. These phenomena also appeared in previous studies (Liao et al, 2020; He et al, 2021b; He et al, 2022), which may be attributed to the material and energy requirements of DIV1 replication and suggested that DIV1 may contain AMGs for regulating host amino acid metabolism, carbohydrate metabolism and energy metabolism. It was worth noting that some pathways related to vitamin metabolism were significantly enriched, such as “retinol metabolism”, “vitamin B6 metabolism” and “pantothenate and CoA biosynthesis”.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In addition, some amino acid metabolism-related pathways were also significantly enriched under DIV1 infection, including “tyrosine metabolism”, “phenylalanine metabolism” and “alanine, aspartate and glutamate metabolism”. These phenomena also appeared in previous studies (Liao et al, 2020; He et al, 2021b; He et al, 2022), which may be attributed to the material and energy requirements of DIV1 replication and suggested that DIV1 may contain AMGs for regulating host amino acid metabolism, carbohydrate metabolism and energy metabolism. It was worth noting that some pathways related to vitamin metabolism were significantly enriched, such as “retinol metabolism”, “vitamin B6 metabolism” and “pantothenate and CoA biosynthesis”.…”
Section: Discussionsupporting
confidence: 75%
“…To date, several crustacean viruses have been found to induce metabolic reprogramming to promote survival and replication, including white spot syndrome virus (WSSV) (Chen et al, 2011; Hsieh et al, 2015; Apún-Molina et al, 2017; Godoy-Lugo et al, 2019), Taura syndrome virus (TSV) (Zeng et al, 2014) and IHHNV (Galvan-Alvarez et al, 2012). In recent years, with global warming and increasing marine pollution, some novel marine viruses have become widespread in the aquaculture industry, causing huge losses to the aquaculture industry (He et al, 2022). Decapod iridescent virus 1 (DIV1) is one of the newly discovered marine viruses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, high-throughput sequencing techniques were used to determine the expression profiles of miRNAs in animals, plants and viruses. Some studies showed that the integrated analysis of miRNA and mRNA in viral infection samples could confirm the regulatory mechanism of miRNA ( 28 30 ). The analysis of giant pandas in captivity vaccinated against CDV was operated with miRNA-mRNA.…”
Section: Discussionmentioning
confidence: 99%